A genus level revision of the Thamnocephalidae (Crustacea: Branchiopoda: Anostraca) - Rogers, D. Christopher (Zootaxa, 2006)
The family Thamnocephalidae, especially the genus Branchinella, has become a mélange of genera and species with unclear affinities. A genus level revision of the family, using modern taxonomic standards, is presented. Two distinct subfamilies are recognized, consisting of six genera (including one new genus): Thamnocephalus and Carinophallus gen. nov. in the Thamnocephalinae, and; Dendrocephalus, Phallocryptus, Gurneya, and Branchinella in the Branchinellinae. Three genera are each composed of two subgenera: Thamnocephalus (Thamnocephalus and Simplicephalus), Dendrocephalus (Dendrocephalus and Dendrocephalinus subgen. nov.), and Branchinella (Branchinella and Branchinellites stat. nov.). A key to the genera is presented coupled with a checklist of all described species in the family, and Branchinella hardingi is redescribed from presumed paratype material.